Addressing vaccine hesitancy among family physicians and Expanded Programme on Immunization managers; A quasi-experimental study - Marangoz, Bahar; Didem Han Yekdes; Muzaffer Eskiocak (Journal of the Pakistan Medical Association, 2025)
Objective: To assess the capacity of family physicians and those associated with the Expanded Programme on Immunisation as managers to cope with cases of vaccine hesitancy. Method: The quasi-experimental study was conducted in Edirne, Turkiye, from May 20 to August 1, 2019, and comprised family physicians and Expanded Programme on Immunisation managers. After evaluating the subjects’ capacity to address vaccine hesitancy, a training course was conducted that had 8 sessions for the physicians and 1 session for the managers. After the intervention, the capacity of the subjects was evaluated again. In assessing the effectiveness of the intervention, relative efficacy, attributed efficacy and efficacy were calculated. Data was analysed using SPSS 22. Results: There were 111 participants with mean age 45±8.9 years (range: 27-70 years) and mean professional experience 19±8.7 years (range: 1-37 years). The participants developed a positive attitude towards getting influenza vaccine for themselves, vaccinating their children with all vaccines, vaccinating their elderly or their relatives with chronic diseases (p<0.05). The participants were positively influenced by the training in terms of motivational interviewing with vaccine hesitancy cases and being prepared for their doubts about the vaccine's necessity, effectiveness, content, safety, side effects and conspiracy theories (p<0.05). Conclusion: Training of family physicians and Expanded Programme on Immunisation managers increased awareness regarding immunisation. Key Words: Vaccine hesitancy, Family physicians, Intervention study, Immunisation.